New challenges for banks in today's world : papers and group discussions (Paris : Association professionnelle des banques, 1975)
This book covers deliberations at the 28th session of the International banking Summer School, held at La Baule, France, from June 2 to 13, 1975.
Includes bibliographical references.
osc 09/05/2018
Loans
Keywords: Banks and banking; Finance